A review of current knowledge and research priorities for conservation of lentic biodiversity in tropical wet and monsoonal urban landscapes. (23rd August 2022) - Gebreselassie, Selam S.; Lechner, Alex M.; Hill, Matthew J.; Teo, Fang Yenn; Gibbins, Christopher N.
Abstract: Urban expansion is a major threat to diversity, especially in rapidly developing tropical countries where urban areas are growing at great pace and protection is limited. We conducted a systematic review of published research on the ecology of lentic habitats in tropical urban areas. The review focused on understanding: (1) how much is currently known about the biodiversity of these habitats; (2) whether this knowledge is biased towards certain taxonomic groups and/or geographic areas; (3) what is known about the factors influencing their diversity; and (4) which ecosystem services urban lentic habitats provide. The review aimed to establish whether existing knowledge is sufficient to help guide conservation and provide evidence to policy makers of the importance of conserving tropical urban wetlands. We found 64 papers that addressed questions about the diversity and/or distribution of lentic ecosystems within tropical urban areas. Papers came from 15 countries, although almost half (45%) were from India; relatively few countries from Southeast Asia, tropical Africa, or South America were represented in the literature. Publication patterns revealed a growing interest in urban wetlands, but several biases and gaps were evident from the review. Firstly, papers generally focused on larger natural or semi‐natural wetlands, with other types and sizes of lentic habitat under‐represented in published work. Secondly, most papers focused on a single site, with a limited number of multi‐site, city‐wide, or landscape‐scale diversity assessments. Thirdly, studies tended to focus on understanding the influence of water quality on diversity, with work assessing the influence of physical habitat or factors related to dispersal and connectivity very limited. Finally, work assessing the ecosystem services provided by wetlands in tropical urban areas remains narrow in focus, with few quantitative assessments of the relationship between ecological characteristics and ecosystem functions and services. We suggest a number of research focal points and approaches to help address these biases. Research is needed to improve understanding of the distribution patterns tropical freshwater species in urban areas and of the relationships between species diversity and a wider set of environmental and spatial conditions. Overall, there is a need for diversity assessments of tropical urban wetlands of all types and sizes, especially new and novel habitats, and scope for much greater adoption of ecosystem service concepts and evaluation tools to help emphasise the importance of these habitats.